From challenge to growth: A qualitative study of parental adaptation to Autism Spectrum Disorder - Chiara Fante; Fabio Fontana; Francesca Capelli; Barbara Dioni; Mattia Pezzi; Cinzia Raffin; Raffaele De Luca Picione; Alessandro Musetti (PLoS ONE, 2026)
Raising a child with Autism Spectrum Disorder (ASD) profoundly affects family dynamics and parental well-being. While research has often focused on stress and negative outcomes, less is known about the processes and resources that foster adaptation and growth in parents. This qualitative study explored the adaptation process among parents of children with ASD, examining both challenges and transformative experiences, and identifying key personal and contextual factors that support or hinder adjustment. Thirty-six parents (19 mothers, 17 fathers) of children aged 5–11 years with ASD (severity level 2 or 3, DSM-5) were recruited from two health care centres for ASD in Northern Italy. Semi-structured interviews were conducted using a guide developed according to an established methodological framework for qualitative interviews and analysed following Braun and Clarke’s framework. Themes were organised into three conceptual domains (i.e., Outcomes, Resources, and Challenges) reflecting the main research aims. Parents reported both emotional distress and personal growth, including improvements in family functioning and child development (Outcomes). Facilitating factors included social support, access to information, professional interventions, and parental self-efficacy (Resources). Barriers included difficulties with services, family conflicts, social stigma, and maladaptive coping strategies (Challenges). Parental adaptation to ASD emerged as a dynamic, ongoing process of negotiation between challenges and resources, often leading to transformative experiences and personal growth. The findings support the implementation of systematic intervention strategies aimed not only at reducing parental stress, but also at empowering parents and promoting the development of adaptive resources.